Browsing Towards Happiness: Determinants of Happiness of Young Millennial Students - A. Mata, Kathlyn (International Journal of Psychosocial Rehabilitation, 2020)
Sources of happiness of young millennial women in Northern Philippines were examined using a sample of female college students. Descriptive survey design was utilized with the Myers-Briggs Type Indicator, a standardized personality test, a structured questionnaire, and document analysis as data-gathering tools. Results showed that the majority of the millennial students’ concept of happiness is equivalent to Abraham Maslow’s third stage of hierarchy of needs, “belongingness and love needs.” Chi-square analysis revealed that some family profile variables are correlated with happiness. Further, the top five sources of young millennial women’s happiness include engagement in social media activities, possession of electronic gadgets, chatting with friends, and listening to music.